2013
DOI: 10.1177/1359105313514285
|View full text |Cite
|
Sign up to set email alerts
|

The importance of authenticity for student non-drinkers: An interpretative phenomenological analysis

Abstract: Our article illustrates the importance of authenticity to student non-drinkers. Semi-structured interviews focussing on the lived experiences of five non-drinking students were subjected to interpretative phenomenological analysis. We present four inter-related themes: 'Retaining authenticity by not drinking', 'Tainting the self by drinking alcohol', 'Feeling trapped by superimposition and self-exposition' and 'Doing what you want to do with your life'. Self-authenticity informed the decision not to drink, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
7
26
0
Order By: Relevance
“…Through finding excuses or avoiding uncomfortable conversations about drinking, participants would not only avoid peer pressure and encouragement to drink, but would also reduce the risk of being excluded from social events with new acquaintances altogether. Our findings are similar to Conroy and de Visser ( 2015 ) in which participants revealed that passing as an alcohol consumer, such as by holding an alcoholic drink was an easier and sensible method as opposed to drawing attention to their non-drinking behaviour.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Through finding excuses or avoiding uncomfortable conversations about drinking, participants would not only avoid peer pressure and encouragement to drink, but would also reduce the risk of being excluded from social events with new acquaintances altogether. Our findings are similar to Conroy and de Visser ( 2015 ) in which participants revealed that passing as an alcohol consumer, such as by holding an alcoholic drink was an easier and sensible method as opposed to drawing attention to their non-drinking behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…As Social Identity Theory (Taijfel and Turner 1986 ) suggests, this may be a result of drinking students making distinctions between themselves, as the in-group, and non-drinkers as the outgroup. These results chime with Conroy and de Visser ( 2015 ), in which their participants expressed frustration having to justify their decision not to drink and having to reveal personal accounts of why there are a non-drinker during conversations with new people.…”
Section: Discussionsupporting
confidence: 67%
“…It is interesting that the importance of self-formation identified here resonates with the findings of some studies of permanent abstinence from alcohol amongst young people or students (e.g. Nairn et al, 2006;Herring et al, 2012;Conroy & De Visser, 2015;Supski & Lindsey, 2016). The manner in which some Dry January participants draw distinctions between different selves (i.e.…”
Section: Resultssupporting
confidence: 84%
“…boring and deviant ). However, this work has also highlighted how non‐drinking may be instrumental in producing valued alternate leisure identities , in bolstering feelings of choice in life and of promoting a stronger sense of authentic self . Indeed, some research has suggested that moderate drinkers may in fact be viewed more negatively than non‐drinkers in that drinking moderately risks presenting oneself as only partially committed to social drinking activities while non‐drinking reduces ‘leg‐room’ for peer pressure to drink excessively .…”
Section: Introductionmentioning
confidence: 94%